Plantas medicinais abortivas utilizadas por mulheres de UBS: etnofarmacologia e análises cromatográficas por CCD e CLAE - Souza Maria, N.c.v.; Tangerina, M.m.p. [UNESP]; Silva, V.c [UNESP]; Vilegas, Wagner [UNESP]; Sannomiya, M. (Sociedade Brasileira de Plantas Medicinais, 2013)
The use of medicinal plants corresponds to an ancient practice, either as an alternative medicine for the cure of several diseases, or as a method of abortion. Nevertheless, the population in general does not know the risks involved in the use of medicinal plants. In this sense, the purpose of the study was to evaluate the consumption rate of medicinal plants by women in a Basic Health Unit (BHU), on order to identify which plant species have been most frequently consumed by them, including during the pregnancy. Through an exploratory questionnaire with 48 women, it was observed that most part of the interviewees had children and the most of them cited Peumus boldus, Baccharis trimera and Cassia angustifolia, which were mainly used for stomach aches or digestives (53%), for colds (23%), menstrual cramps (4%) or to menstruate (2%). The remaining part of the study consisted in the visual and chemical analysis of the plant species cited by the interviewees, including other species that have been popularly used as a method of abortion. Comparative visual analysis of medicinal plants (Group A-C) from four different shops showed the absence of quality control concerning packing specifications and the separation of the plant material to be consumed. The analysis of the chemical profiles of these samples by thin layer chromatography (TLC) and high performance liquid chromatography (HPLC) indicated that those species belonging to the Group C were significantly different from those plants having the same identification, except for Peumus boldus, whose samples were similar in terms of chemical composition.

O emprego de plantas medicinais refere-se a uma prática milenar, seja na medicina alternativa para cura de diversas doenças, ou como método abortivo. No entanto, a população em geral desconhece os grandes riscos que a cometem. Neste sentido este trabalho teve como objetivo avaliar o índice de consumo de plantas medicinais por mulheres de uma Unidade Básica de Saúde (UBS), na tentativa de identificar quais as espécies mais frequentemente ingeridas inclusive em período gestacional. Através de um questionário de caráter explorativo com 48 mulheres observou-se que a maioria das entrevistadas tinha filhos e as plantas medicinais mais citadas foram boldo (Peumus boldus), carqueja (Baccharis trimera) e sene (Cassia angustifolia), as quais eram empregadas principalmente em dores estomacais ou como digestivos (53%), para resfriados (23%), cólicas menstruais (4%) ou para menstruar (2%). Outra parte do trabalho constituiu a análise visual e química de espécies de plantas medicinais citadas pelo público feminino entrevistado, bem como, outras utilizadas popularmente com propriedades abortivas. Análises visuais comparativas de amostras de plantas medicinais de quatro estabelecimentos comerciais diferentes denominadas Grupo A-C, mostraram a ausência de controle de qualidade com relação às especificações nas embalagens, e separação do material vegetal a ser consumido. Através de análises dos perfis químicos destas amostras por cromatografia em camada delgada (CCD) e cromatografia líquida de alta eficiência (CLAE) indicaram que aquelas pertencentes ao Grupo C diferiram significativamente em relação àquelas de mesma identificação, exceto no que se refere ao boldo do Chile, cujas amostras apresentaram-se bastante similares com relação à constituição química.
Abortive medicinal plants used by women of Basic Health Units: ethnopharmacology and cromatographic analysis by TLC and HPLC
Keywords: mulheres; UBS; plantas medicinais; abortivas; women; medicinal plants; bortive plants